Assessing the misuse in neighborhood open space according to park by laws (MBPJ 2005) - Ibrahim, Putri Haryati; Zulkifli, Nabilah Huda (Kulliyah of Architecture and Enviromental Design, International Islamic University Malaysia, 2018)
Parks is an example of open spaces where people can enjoy active and passive activities during free times to runway from the hustle and bustle of the cities. Policies and guidelines have been implemented by the local authorities so that the public parks and open spaces in their area of jurisdiction are convenience to be used as well as to ensure public safety. This study aimed to identify and understand; misuse of neighbourhood open spaces in the area of Majlis Bandaraya Petaling Jaya (MBPJ) jurisdiction according to the Parks Bylaws (MBPJ 2005). Six (6) open spaces have been chosen namely; Taman Jaya in Section 10, several neighbourhood open spaces located at Section 13, Section 14, Section 17, Section 19 and last but not least, Taman Aman in Section 22. The methodologies used are questionnaire survey that obtained a sample size of 90 respondents and in-depth interview session with the officers from the Landscape Department of MBPJ. This study found that; illegal dumping, vandalism, and illegal placement of posters and advertisements are the main offenses occur in the neighbourhood open spaces while illegal parking, indecent behaviour and walking the dogs in the parks were found to be the example of minor offences happened. This study noticed that violation of Parks Bylaws occurred mainly due to lacking of awareness and public involvement. The study also outlined several suggestions to address the issues encountered in order to reduce problems regarding the misuse of open spaces that perhaps can lead to the betterment usage of the areas.